Visual art and participatory culture : the case of Château Nour in Brussels - Saccani, Marta (2021)
Taking into account the migration crisis Europe has been facing, analysing and developing methods of active and positive inclusion to foster integration is necessary for Europe to remain a democratic and inclusive place. This research proposes an analysis of how cultural non-profit associations through artistic practices are in constant dialogue with the communities and spaces around them. Central to the research is the concept of art democratization, which is explored in the sense of need for inclusion. The artistic object itself must stop being an ‘enclaved commodity’ (Appadurai 2013) and its ‘symbolic power’ (Appadurai 2013) has to change in a more comprehensive way. As a case study, Brussel-based artistic space Chateau Nour is analysed. Among the non-profit associations Chateau Nour hosts, Rectangle and the social activities it engages in are taken into consideration as a key study, thanks to the work experience made during my internship from 01/09/2019 to 31/12/2019. By exploring the conceptual field of relational and participatory cultural practices, this research discusses the notion of the image and its role in the public space to understand if this medium can be considered as relational. This concept, which symbolises a consistent part of the artistic field, is chosen as a tool of investigation because of how it is critically utilized by the non-profit association Rectangle, where I did my internship. Since its creation, Rectangle has challenged the use of the image, of advertising language and of how its apparatus is displayed in the public space. Rectangle, in fact, focuses on projects consisting in posters showed on publicly exposed billboards or on the vitrine of Chateau Nour. In this way the artistic show is not anymore a privileged spot or a privileged moment. If the power of the image is considered, these types of action have social implications of involvement and inclusivity which could be particularly important in socially problematic neighbourhoods.